2021
DOI: 10.3390/biom11020142
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Profiles of Tph1A and BDNF in Gut and Brain of L. Rhamnosus-Treated Zebrafish

Abstract: The bidirectional microbiota–gut–brain axis has raised increasing interest over the past years in the context of health and disease, but there is a lack of information on molecular mechanisms underlying this connection. We hypothesized that change in microbiota composition may affect brain epigenetics leading to long-lasting effects on specific brain gene regulation. To test this hypothesis, we used Zebrafish (Danio Rerio) as a model system. As previously shown, treatment with high doses of probiotics can modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Disentangling this phenomenon requires technical approach that may be challenging. In our previous works 13 17 , we demonstrated that the analysis of epiallele distribution may be considered a proxy of single cell studies, since epialleles represent the specific combination of methylated and unmethylated CpGs at single molecule levels. Therefore, evaluating the distribution of epialleles may mirror the different cellular composition in a given tissue and may identify DNA methylation differences among cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disentangling this phenomenon requires technical approach that may be challenging. In our previous works 13 17 , we demonstrated that the analysis of epiallele distribution may be considered a proxy of single cell studies, since epialleles represent the specific combination of methylated and unmethylated CpGs at single molecule levels. Therefore, evaluating the distribution of epialleles may mirror the different cellular composition in a given tissue and may identify DNA methylation differences among cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, DNA methylation at Fxyd1a increased during brain development and decreased during heart development in line with changes of mRNA expression levels. We have previously demonstrated that ultra-deep methylation analysis may help to unravel cell-to-cell heterogeneity in terms of DNA methylation 13 17 . By using a newly generated bioinformatic tool 18 , we were able to assess the quantitative and qualitative distribution of epialleles, intended as combination of methylated and unmethylated CpG sites on the same molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Cuomo et al documented that the administration of L. rhamnosus in larvae led to DNA methylation code of the Tph1A and BDNF promoter gene reconstruction in the gut and the brain of zebrafish. Accordingly, alterations in the gut microbiome may influence the host epigenetic landscape, resulting in long‐term consequences for specific gene regions 32 …”
Section: The Roles Of the Gut Microbiome In Tissue Development And Ph...mentioning
confidence: 99%
“…We used deep amplicon bisulfite sequencing (D-ABS) data to synthesize 4-CpG low coverage datasets, starting from an in-house database of D-ABS amplicons produced in previously published studies (27,(44)(45)(46). Detailed descriptions of the employed amplicons can be found in Supplementary Table 1.…”
Section: Establishment Of MC Profiling Thresholdsmentioning
confidence: 99%